Solving Fractional Damped Burgers' Equation Approximately by Using The Sumudu Transform (ST) Method - Wurood Riyadh Abd AL- Hussein; Rand Muhaned Fawzi (مجلة بغداد للعلوم)
In this work, the fractional damped Burger's equation (FDBE) formula    = 0,